The King Edward Point Geodetic Observatory in Support of Sea Level Research - TEFERLE, Felix Norman; HUNEGNAW, Addisu; AHMED, Furqan; Woodworth, Philip L.; Foden, Peter R.; Williams, Simon D. P. (2013)
During February 2013 the King Edward Point (KEP) Geodetic Observatory was established in South Geor- gia, South Atlantic Ocean, through a University of Luxembourg funded research project and in collaboration with the United Kingdom’s National Oceanography Centre, British Antarctic Survey and Unavco, Inc. Due to its remote location in the South Atlantic Ocean, as well as, being one of few subaerial exposures of the Scotia plate, South Georgia Island has been a key location for a number of global monitoring networks, e.g. seismic, geomagnetic and oceanic. However, no geodetic monitoring station has been established, e.g. by the International Global Navigation Satellite System (GNSS) Service (IGS) community, despite the lack of such observations from this region. In this study we give details of the establishment of the KEP Geodetic Observatory, i.e. the installation of the continuous GNSS station KEPA on Brown Mountain and the estab- lishment of a new height datum for the tide gauge through a network of benchmarks at the KEP research station. We will present an evaluation of the GNSS positioning results for the period from February to August 2013 and of the survey/levelling work carried out for the height reference. We will discuss the installation in terms of its potential contributions to sea level observations using tide gauges and satellite altimetry, studies of tectonics, glacio-isostatic adjustment and atmospheric processes. F1R-ING-PUL-12GSCG > GSCG > 01/04/2012 - 31/03/2015 > TEFERLE Felix Norman